Kritička obeležja i teorijska uporišta kritičko-esejističkog opusa Miroslava Egerića - Bulatović, Boris (Slavistična revija, 2012)
In addition to the overview of Egerić's theoretical insights about literature, the paper provides an analytical presentation of the major determinants of his critical process. Specifically, the following characteristics are singled out and elucidated: (1) creative activism of ethical-existential interpretation; (2) striving for democratic (anti-dogmatic) nature of artistic act; (3) emphasis on historical context as a significant factor in interpreting literary and literary critical works concerned with ethical and existential issues; (4) demonstra- tion of a broad approach in the analysis of one-sided critical principles of Serbian literary critics.
Keywords: avtonomija umetnosti; Egerić, Miroslav, 1934-; ideološka kritika; literarna kritika; literarna teorija; literarni kritiki; literary criticism; literary theory; srbski literarni kritiki; zgodovinski kontekst